Poverty—A structural problem of developing countries - Gabriele Wülker (Intereconomics, 1981)
The contrast between industrialized and developing countries is often seen as one between two opposites: Rich countries—poor countries. But the poverty in the developing countries is by no means identical with the need for help as perceived in the industrialized societies. Poverty in the Third World is, as the following article shows, a structural problem.
Keywords: 330; Development Strategy